PENERAPAN METODE GAMIFIKASI DENGAN MEDIA CANVA DALAM MENULIS TEKS EKSPLANASI UNTUK MENINGKATKAN MOTIVASI DAN PARTISIPASI PESERTA DIDIK PADA FASE C DI SDN KARANGJAYA II - Kharisma Bintang Destriadi Kharisma; Panca Pertiwi Hidayati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study was motivated by the low level of students’ motivation and participation in learning to write explanatory texts in Phase C at SDN Karangjaya II. This condition was influenced by the use of conventional learning methods that did not actively engage students and did not optimally utilize digital media. This study aimed to describe the implementation of the gamification method using Canva media in learning to write explanatory texts, to analyze its effect on students’ writing skills, and to determine the improvement of students’ motivation and participation after the implementation of the method. This research employed a quasi-experimental method with a Nonequivalent Control Group Design. The population of this study consisted of all Phase C students at SDN Karangjaya II. The sample included one class as the experimental group, which received treatment through the gamification method using Canva media, and one class as the control group, which was taught using the expository method. The data was collected using explanatory text writing skill tests (pre-test and post-test), questionnaires on students’ motivation and participation, and documentation and analysed using SPSS 25. The result of the study indicated that the significance value is less than 0.05, meaning that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Therefore, it can be concluded that the implementation of the gamification method using Canva media has a significant effect on students’ ability to write explanatory texts. In addition, the gamification method using Canva media is proven to improve students’ motivation and participation in learning to write explanatory texts in Phase C at SDN Karangjaya II.